Fish Losses of Euthynnus affinis Products at The Fish Landing Base Karangsong Indramayu, West Java - Mohammad Sayuti; Randi Bokhy Syuliana Salampessy; Fajar Ridzki (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2022)
Euthynnus affinis is one of the most loved fish by the community. Fulfillment of the demand for tuna from the process of catching until it is landed for sale has the potential to experience a decrease in yield. The purpose of this study was to determine handling techniques, determine quality, and determine yield losses in tuna catches at the Karangsong Indramayu Fish Landing Base (PPI) West Java. The research was conducted by directly observing the handling process, observing the cold chain of tuna from unloading to loading, conducting organoleptic quality testing, ALT, TVB and calculating fish losses by referring to the Load Tracking (LT) method. The calculation of yield loss is carried out in three types, namely: physical loss, quality loss, and financial loss. The flow of the tuna handling process observed is the unloading process to the loading process. The value of the organoleptic quality test on tuna caught was 8, the ALT test value of the lowest average value was 16,000 col/g and the highest value was 35,000 col/g. The lowest average TVB test value was 9.96 mgN/100 g and the highest was 11.19 mgN/100 g. Euthynnus affinis from unloading to loading experienced physical, quality and financial losses of: 1.07%; 0.84%; and 2.05%.